Sensitivity analysis of offshore wind farm operation and maintenance cost and availability - Martin, Rebecca; Lazakis, Iraklis; Barbouchi, Sami; Johanning, Lars (Renewable energy, 2016)
Operation and Maintenance (O&M) costs are estimated to account for 14%–30% of total Offshore Wind Farm (OWF) project lifecycle expenditure according to a range of studies. In this respect, identifying factors affecting operational costs and availability are vital for wind farm operators to achieve the most profitable decisions. Many OWFs are built in stages and the important factors may not be consistent for the different phases. To address this issue, three OWF case studies are defined to represent two phases and a complete project. An initial qualitative screening sensitivity analysis was conducted to identify the most important factors of O&M affecting operating cost and availability. The study concluded that the important factors for total O&M cost were access and repair costs along with failure rates for both minor and major repairs. For time-based availability, the important factors identified were those related to the length of time conducting the maintenance tasks, i.e. the operation duration and the working day length. It was found that the two stages had similar results, but these were different compared to the complete project. In this case, the results provide valuable information to OWF operators during the project development and decision making process. •Three O&M offshore wind farm phases are subject of a screening sensitivity analysis.•O&M input factor uncertainty are defined using industry knowledge and literature.•The most important factors include failure rates, vessel numbers and costs.•The most important factors are not the same across the different phases.